2013
DOI: 10.14214/sf.958
|View full text |Cite
|
Sign up to set email alerts
|

Simulated productivity of one- and two-armed tree planting machines

Abstract: Simulated productivity of one-and two-armed tree planting machinesErsson B. T., Jundén L., Bergsten U., Servin M. (2013). Simulated productivity of one-and two-armed tree planting machines. Silva Fennica vol. 47 no. 2 article id 958. 23 p. Highlights• Using discrete-event simulation and detailed terrain and machine models, the productivities of excavator-based one-and two-armed tree planting machines were simulated.• The machines' arms were equipped with one-and two-headed planting devices.• Two planting heads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Cost-efficiency is hampered by low productivity, which originates from operator inexperience, among other reasons [12]. The choice of worksites also strongly influences productivity, and it has been reported that the presence of stones, slash, and stumps decreases the planting machines' productivity [13][14][15][16][17]. The size and spatial distribution of worksites also affects cost-competitiveness [18].…”
Section: Introductionmentioning
confidence: 99%
“…Cost-efficiency is hampered by low productivity, which originates from operator inexperience, among other reasons [12]. The choice of worksites also strongly influences productivity, and it has been reported that the presence of stones, slash, and stumps decreases the planting machines' productivity [13][14][15][16][17]. The size and spatial distribution of worksites also affects cost-competitiveness [18].…”
Section: Introductionmentioning
confidence: 99%
“…In essence, this study used the models and discrete-event simulation tool described mainly in Ersson et al (2013) but also in Jundén (2011). Explained below are the additions and improvements made to the models for this specific study, and its experimental design.…”
Section: Methodsmentioning
confidence: 99%
“…The two-headed M-Planter attaches to an excavator's crane; mounds and then deep-plants seedlings; and has reached productivities exceeding 300 seedlings per productive work hour (pl/PWh, excluding delays) during time studies on clearcuts where stump and slash had been harvested (Laine & Rantala 2013). Ersson et al (2013) reported a theoretical productivity over 400 pl/PWh when the M-Planter was simulated on obstacle-sparse terrain, and this figure was about 60% higher than that of the one-headed Bracke Planter. Nonetheless, follow-ups of practical work with the MPlanter have noted average productivity figures only half as high as the theoretical ones (Rantala & Laine 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stones, stumps, slash and roots impede e.g. site preparation and mechanized planting (Larsson 2011;Luoranen et al 2011;Ersson et al 2013) whereas some of these objects need to be located efficiently for other purposes than avoidance, e.g. during slash forwarding and stump removal.…”
Section: Introductionmentioning
confidence: 99%